Early stimulated thyroglobulin for response prediction after recombinant human thyrotropin-aided radioiodine therapy - Park, Hee Jeong (Ann Nucl Med, 2017)
OBJECTIVE: Measurement of recombinant human thyrotropin (rhTSH)-stimulated thyroglobulin (Tg) is generally recommended 72 h after the second rhTSH injection. However, due to the acute effect of I-131 on thyrocytes, Tg measured after radioiodine therapy (RIT) would not accurately reflect the thyroid tissue burden. We aimed to determine predictive values of serum Tg level measured just before rhTSH-aided RIT and to compare the results obtained just after RIT in patients with differentiated thyroid carcinoma (DTC). METHODS: We evaluated 150 patients with DTC who underwent rhTSH-aided RIT (2.96–6.66 GBq) after total thyroidectomy between 2009 and 2014. Serum Tg level was measured 24 h (early Tg) and 72 (or 96) h (delayed Tg) after the second rhTSH injection. An excellent response was defined based on the latest American Thyroid Association Guidelines. Univariate and multivariate analyses were performed for early Tg, delayed Tg, and other clinical variables. RESULTS: In the multivariate analysis, tumor size [odds ratio (OR) 1.716; 95% confidence interval (CI) 1.019–2.882; p = 0.042] and early Tg level (OR 2.012; 95% CI 1.384–2.925, p < 0.001) independently predicted excellent responses. The cutoff for the best early Tg level to predict a non-excellent response was 2.0 ng/mL. Delayed Tg was not a significant predictor (OR 0.992; 95% CI 0.969–1.015; p = 0.492). CONCLUSIONS: Early stimulated Tg significantly predicted therapeutic response after rhTSH-aided RIT in patients with DTC. Therefore, serum Tg should be measured before RIT to predict therapeutic responses.